The incidence of isthmocele may be higher than reported - Karlı, Pervin; Şahin, Banuhan; Kara, Fadıl (Journal of Surgery and Medicine, 2018)
Aim: Isthmocele, a long-term complication of Cesarean section (CS) surgery, has drawn increasing worldwide interest. However, not all women with this Cesarean scar defect (CSD) present with clinical symptoms. We studied a group of non-pregnant women with a CS history to determine the prevalence of isthmocele, the potential risk factors for its development, and the most common clinical complaints. Methods: This study included women who had a cesarean operation more than 6 months ago, who were not pregnant between January 2017 and April 2017 and applied to the gynecology clinic for any reason. The exclusion criteria were the patients in the menopause period. Data was collected on 115 participants, including age, body mass index, duration after CS, and the number of CS surgeries that had been performed. Standardized scar parameters (residual myometrial thickness (RMT) and the depth and width of the triangular hypoechoic niche) were measured using transvaginal-ultrasonography (TVS). Isthmocele symptoms were categorized as asymptomatic, postmenstrual spotting, menometrorrhagia, chronic pelvic pain, dysmenorrhea, and infertility. Associations between isthmocele and menstrual complications were investigated. The relationship between isthmocele development and the reasons for the CS surgery were evaluated. Results: TVS examination diagnosed 17 women (14.78%) with isthmocele. Women who had undergone recurrent CS surgeries tended to have more visible isthmocele than those with a single CS surgery. The average isthmocele depth was 6.006 ± 0.7970 mm. Among the women with isthmoceles, elective CS surgery had been performed in six (35.3%), while 11 (64.7%) had the surgery at parturition. The presence of an isthmocele was frequently symptomatic, predominantly as postmenstrual spotting. Women with an isthmocele had significantly lower RMT values (5.57 ± 0.60 mm versus 8.78 ± 0.22 mm) than those without an isthmocele. There was no correlation between age, body mass index, and the presence of an isthmocele (p > 0.05). Conclusions: The incidence and prevalence of CSD is greater than most gynecologists realize. Isthmoceles can develop after just one CS surgery, leading to long-term complications that morbidly effect women for the rest of their lives. A reduction in the number of CS surgeries is the most effective way to decrease the prevalence of isthmoceles.